Electrochemical learning with a modified writing to teach (WtT) approach to improve the students' concept mastery. (March 2020) - Nurdiyanti, D; Permanasari, A; Mulyani, S; Hernani
Abstract: Concept mastery is considered as a requirement that must be possessed by chemistry teacher candidates to teach the students about chemical concepts. The aim of this study is to improve the students' concept mastery in electrochemistry through school chemistry subject by conducting a modified WtT approach. The study involves twenty students in the fifth semester who commit the subject of school chemistry. The data are obtained through test of concept mastery to obtain information about the concept of mastery of before and after learning. Then, the data are carried out from interview to obtain information about the students' responses in related to the implementation of WtT approach in the learning process. The data analysis is accomplished through the N-Gain test to discover the improvement of the implementation of concept mastery and effect size test for paired t-test to determine its effectiveness. Meanwhile, the results of interview are utilized to strengthen the data of concept mastery. The results of the present study reveal that there is an average improvement of the students' concept mastery. Furthermore, the result of effect size test shows that the WtT approach is considered to be effective to improve the students' concept mastery in the average level.